Diet-Gene Interactions in Farm Animals: Molecular Dynamics, Gene Expressions, Signalling Pathways and Precision Nutrition for Sustainable Productivity - Md. Emran Hossain (International Journal of Genetic Modifications and Recombinations, 2026)
Diet-gene interactions represent a central mechanism through which nutrition influences growth, health, and productivity in farm animals. Recent advances in molecular biology and genetics have revealed that nutrients act not only as metabolic substrates but also as signalling molecules capable of modulating gene expression, cellular pathways, and epigenetic regulation. This review synthesizes current knowledge on the molecular dynamics of nutrient utilization in farm animals, with emphasis on nutrigenomic responses, nutrient sensing mechanisms, and key signalling pathways involved in metabolism, immunity, and stress adaptation. Major regulatory pathways, including mTOR, AMPK, insulin, and insulin like growth factor signalling, are discussed in relation to dietary modulation and genetic variation among species and breeds. The role of epigenetic mechanisms and gut microbiome interactions in mediating diet induced genetic responses is also highlighted. Furthermore, the application of omics technologies in elucidating complex diet-gene networks and their relevance to precision nutrition strategies is critically evaluated. By integrating molecular, genetic, and nutritional perspectives, this review provides a comprehensive framework for understanding diet-gene interactions and identifies future research directions for improving efficiency, resilience, and sustainability in farm animal production systems.
Keywords: Epigenetics; farm animals; gene expression; molecular nutrition; nutrient signalling; nutrigenomics